Plagiarism in academia: A persistent ethical challenge - Subedi, Suraksha; Ranjit, Rebicca (Journal of Gandaki Medical College-Nepal, 2026)
Plagiarism is a form of intellectual theft that occurs when an individual uses another person's ideas, words, or work without giving proper credit to the original source. It is a serious violation of academic integrity and ethical standards, often resulting in significant academic, professional, and legal consequences. Understanding plagiarism and its various forms is essential for maintaining honesty and credibility in both academic and professional settings.